2019
DOI: 10.1016/j.physbeh.2017.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Sex- and dose-dependent abuse liability of repeated subanesthetic ketamine in rats

Abstract: These data suggest that in rats, six alternating-day treatments with 2.5mg/kg KET do not induce apparent behavioral signatures of abuse liability despite accumulation of ΔFosB protein in the accumbens. Additionally, females are more sensitive than males to KET's locomotor-stimulant properties, both acutely and after repeated treatments. More studies are needed to determine brain regions and neural mechanisms responsible for KET-induced behavioral adaptations and to extrapolate these data to inform sex-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 92 publications
3
41
0
Order By: Relevance
“…Locomotor sensitization after repeated exposure to drugs of abuse is indicative of plasticity in the reward circuitry that may underlie the transition to addiction. Interestingly in these studies, the same rats that displayed sensitization did not form a CPP to ketamine at any dose tested [62,63]; in fact, females displayed a conditioned place aversion to 5.0 mg/kg. Together, these findings suggest that divergent mechanisms may underlie the locomotor activating effects and the associative rewarding effects of ketamine.…”
Section: Sex Differences In the Anti-depressant Activity Of Ketaminementioning
confidence: 88%
See 1 more Smart Citation
“…Locomotor sensitization after repeated exposure to drugs of abuse is indicative of plasticity in the reward circuitry that may underlie the transition to addiction. Interestingly in these studies, the same rats that displayed sensitization did not form a CPP to ketamine at any dose tested [62,63]; in fact, females displayed a conditioned place aversion to 5.0 mg/kg. Together, these findings suggest that divergent mechanisms may underlie the locomotor activating effects and the associative rewarding effects of ketamine.…”
Section: Sex Differences In the Anti-depressant Activity Of Ketaminementioning
confidence: 88%
“…Female rats show increased locomotor sensitization to intermittent (weekly and every other day, respectively) repeated ketamine at depression-relevant doses (2.5-10.0 mg/kg intraperitoneally, i.p.) [62,63]. Locomotor sensitization after repeated exposure to drugs of abuse is indicative of plasticity in the reward circuitry that may underlie the transition to addiction.…”
Section: Sex Differences In the Anti-depressant Activity Of Ketaminementioning
confidence: 99%
“…Additionally, depression is twice as prevalent in women as compared to men ( Whiteford et al, 2013 ), is highly comorbid with addiction ( Ng et al, 2017 ), and women who recreationally abuse ketamine report more severe symptoms during withdrawal from ketamine, concomitant substance use, and more cognitive impairments when compared to men ( Chen et al, 2014 ). As we will discuss later, animal studies have also reported a heightened sensitivity to antidepressant and addictive effects of ketamine in females compared to males ( Carrier and Kabbaj, 2013 ; Franceschelli et al, 2015 ; Schoepfer et al, 2017 ; Strong et al, 2017 ; Zanos et al, 2016 ). The meta-analysis mentioned above analyzed gender and age as factors across the 11 studies and found no effect of either ( Cho et al, 2005 ), and a recent report found no evidence of gender nor age being significant predictors of ketamine's antidepressant efficacy ( Niciu et al, 2014 ).…”
Section: The Addictive Potential Of Repeated Low-dose Ketamine Infusimentioning
confidence: 97%
“…when compared to males (5 mg/kg, i.p.) ( Schoepfer et al, 2017 ). Interestingly, behavioral sensitization in both sexes was positively correlated with ΔfosB –a marker of long-term plasticity-expression in the NAc ( Schoepfer et al, 2017 ).…”
Section: The Addictive Potential Of Repeated Low-dose Ketamine Infusimentioning
confidence: 99%
“…However, chronic ketamine (20 mg/kg, twice a day) in the adolescent rat was also reported to endure resilience and presumed useful as an antidepressant [23]. Of note, repeated administration of 10 mg/kg dose was recently shown to elicit condition place preference in male rats [24]. In previous studies, behavioral evaluation was usually focused on domains related to attention, working memory, problem solving and social deficits [17], while anxiety-like symptoms were mostly neglected [3].…”
Section: Introductionmentioning
confidence: 99%